2020
DOI: 10.18683/germs.2020.1217
|View full text |Cite
|
Sign up to set email alerts
|

Comment on: "The relationship between the exposure to healthcare settings and colonization with methicillin-resistant Staphylococcus aureusamong medical students”

Abstract: This article 1 provides crucial insights into the ways in which medical students undergoing clinical placement might pose a risk to patients. The authors have identified a key issue in the clinical teaching setting whereby medical students are unknowing carriers for methicillin-resistant Staphylococcus aureus (MRSA), and therefore contributing to the potential spread of this deadly infection to vulnerable patients. Medical students often spend much time with patients as part of their training, involving extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Some articles also used nutrient broth for bacterial growth, such as brain heart infusion agar with the presence of NaCl at 7,5%, tryptone soy broth enriched agar and mannitol salt agar, quoted sequentially as Jayaweera et al (2020), López-Aguilera et al (2013), Ho, Lai and Chow (2015), and Budri et al (2018). The methodology presented in each article is resumed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some articles also used nutrient broth for bacterial growth, such as brain heart infusion agar with the presence of NaCl at 7,5%, tryptone soy broth enriched agar and mannitol salt agar, quoted sequentially as Jayaweera et al (2020), López-Aguilera et al (2013), Ho, Lai and Chow (2015), and Budri et al (2018). The methodology presented in each article is resumed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, other studies have also shown a significantly association between MRSA transport and time of exposure to the hospital. In Jayaweera et al (2020), three batches of medical students, from first, third and fifth year, were screened for MRSA colonization. Before having been exposed to healthcare settings, only 6.4% of 1 st year students were MRSA carriers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation